Islamic Education as a Catalyst for Societal Transformation in the Digital Age - Prayitno Prayitno; Mira Mahmudah; Mar’ah Sapitri; Sudin Sanjaya (Pusat Publikasi Nusantara, 2026)
The societal transformation currently taking place in the world is highly complex, driven primarily by advances in digital technology, globalization, and demographic change. Islam, with the second-largest religious following — comprising approximately 25% of the world's population, or roughly 2 billion people — can play a significant role in this transformation and become a moral and spiritual force in creating a just, noble, solidary, and ethical society through the application of values such as honesty, responsibility, justice, and transformative education and leadership, encouraging positive innovation while maintaining the noble values of religion amidst changing times, especially in the digital era. In a global context, Islam has proven to be a catalyst for transformation throughout its history, such as during the golden age of Islamic civilization in the Middle Ages, which combined science, philosophy, and spirituality for social progress. This study aims to identify and promote the role of Islamic education in social transformation and to contribute positively to the advancement of society while remaining relevant to changing times through a dynamic and transformative approach. This study uses the Systematic Literature Review (SLR) method with data drawn from Scopus and visualized using VOSviewer software to analyze previous research related to this research topic and identify research gaps in prior research. This study also uses a qualitative literature review method that critically examines, analyzes, and synthesizes knowledge or findings from various academic literature and is enriched with thematic analysis to identify key patterns from primary and secondary sources to ensure accuracy.